Mantle cell lymphoma involving the oral and maxillofacial region: a study of 20 cases - Carvalho, Marcus Vinícius Ribeiro; Rodrigues-Fernandes, Carla Isabelly; de Cáceres, Cinthia Veronica Bardález López; Mesquita, Ricardo Alves; Martins, Manoela Domingues; Román Tager, Elena María José; Carlos, Roman; Pires, Fábio Ramôa; Robinson, Liam; van Heerden, Willie F.P.; Valente, Vitor Bonetti [UNESP]; Xavier-Júnior, José Cândido Caldeira; et al. (Elsevier, 2023)
Objective: To investigate the clinicopathologic features of mantle cell lymphoma (MCL) involving the oral and maxillofacial region. Methods: The MCL cases were retrieved from the pathosis database of 6 pathology laboratories. Original hematoxylin and eosin slides and immunohistochemical reactions were reviewed for confirmation of the initial diagnosis. Clinical data of the cases were obtained from the patients’ pathosis and/or medical charts. Results: Twenty cases were included in the study, showing a male predominance and a mean age of 66 years. The oral cavity (12 cases) and the oropharynx (5 cases) were the most commonly involved subsites. Most cases presented as asymptomatic swellings, with 2 cases showing bilateral involvement of the palate. The classic histologic variant predominated (12/20 cases). All cases expressed CD20 with nuclear cyclin D1 positivity. SOX11 was seen in 9/13 cases, CD5 in 6/16 cases, Bcl2 in 16/19 cases, CD10 in 2/20 cases, and Bcl6 in 4/16 cases. Ki67 showed a mean proliferation index of 40.6%. The Epstein-Barr virus (EBV) was negative in all cases investigated. Follow-up data was available for 7 patients, with 5 currently alive and 2 deceased. Conclusion: Mantle cell lymphoma, albeit rare, may manifest in the oral and maxillofacial region. Its histologic heterogeneity demands a high degree of diagnostic skill from pathologists.